Sarcoma histiocítico em cães - Luz, Flávia Serena da (2022)
Histiocytic sarcoma is a malignant, progressive, and uncommon neoplasm that is part of a group of proliferative histiocytic diseases. This form of cancer originates from histiocytic cells, such as antigen-presenting cells, including Langerhans cells, and macrophages. The tumor can affect different species, but it is most commonly diagnosed in dogs. Epidemiologically, it is known that there is a predilection for large dogs and for some specific breeds, such as the Bernese Mountain dog. Article 1 of this thesis presents the results of a retrospective study aimed at definitively diagnosing and characterizing the epidemiology, anatomopathology and immunophenotypic behavior of histiocytic sarcoma. Histopathology results were obtained that reinforce some classic concepts, such as the importance in the presence of mono, bi and multinucleated giant cells for a strong diagnostic suspicion, as well as others that expand the knowledge about this form of cancer, such as the predisposition in Rottweiler dogs. Article 2 of this thesis presents the description of three cases of hemophagocytic histiocytic sarcoma, a rare variant that leads to hemolytic crisis and its consequences. The diagnosis was made by the association of clinical, laboratory, anatomopathological, and immunohistochemistry. In both articles it was possible to describe the immunophenotypic behavior of neoplastic cells against markers CD204, MHC-II and CD11d. Histiocytic sarcoma has become an increasingly frequent diagnosis in dogs in the routine of the laboratory of veterinary pathology, presenting itself as an interesting form of cancer to be studied, for a better understanding of its pathogenic mechanisms and variations regarding to immunophenotyping.